Girolline is a sequence context-selective modulator of eIF5A activity - Tilman Schneider-Poetsch; Yongjun Dang; Wakana Iwasaki; Mayumi Arata; Yuichi Shichino; Ali Al Mourabit; Celine Moriou; Daniel Romo; Jun O. Liu; Takuhiro Ito; Shintaro Iwasaki; Minoru Yoshida (Nature Communications, 2025)
Abstract Natural products have a long history of providing probes into protein biosynthesis, with many of these compounds serving as therapeutics. The marine natural product girolline has been described as an inhibitor of protein synthesis. Its precise mechanism of action, however, has remained unknown. The data we present here suggests that girolline is a sequence-selective modulator of translation factor eIF5A. Girolline interferes with ribosome-eIF5A interaction and induces ribosome stalling where translational progress is impeded, including on AAA-encoded lysine. Our data furthermore indicate that eIF5A plays a physiological role in ribosome-associated quality control and in maintaining the efficiency of translational progress. Girolline helped to deepen our understanding of the interplay between protein production and quality control in a physiological setting and offers a potent chemical tool to selectively modulate gene expression.